Phygitally Yours: Examination of Virtual Reality Experiences in Digital Sports and Recreational Games - Y ¼ce, Arif; AydoÄŸdu, Volkan; G ¶kce Y ¼ce, Sevda; KatÄ±rcÄ±, Hakan (Jurnal The Messenger, 2021)
The demand for, and investment in digital virtual reality (VR) games, both by companies and consumers, are increasing day by day. Accordingly, understanding the experiences created by VR within the scope of phygital marketing is important in terms of contributing to virtual experiential marketing, marketing communication, recreation and similar fields. The concept of phygital, expresses the integral wholeness of the digital and physical. And Phygitally Yours refers to individuals who can live in their own phygital worlds in today's technologies. The aim of this study was to examine the experiences created by digital games involving sports and recreational content within the scope of phygital marketing. Eight individuals who did not have any prior VR experience played digital games with sports (Grand Turismo Sport) and recreational (VR Worlds) content using VR glasses. Subsequently, in-depth interviews were conducted. The data were analysed using the content analysis method, and thematic codes and concepts were revealed and interpreted. As a result of the research, it was determined that the participants' first VR experience of digital games involved the dimensions of sense, interaction, pleasure and flow, with the following codes emerging: perfect holistic effect, showroom feeling, understandable, competition, magic, gorgeous, dilemma, and place independent behaviour.